2016
DOI: 10.1038/nrmicro.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of biodiversity in the Earth mycobiome

Abstract: Fungi represent a large proportion of the genetic diversity on Earth and fungal activity influences the structure of plant and animal communities, as well as rates of ecosystem processes. Large-scale DNA-sequencing datasets are beginning to reveal the dimensions of fungal biodiversity, which seem to be fundamentally different to bacteria, plants and animals. In this Review, we describe the patterns of fungal biodiversity that have been revealed by molecular-based studies. Furthermore, we consider the evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
402
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(424 citation statements)
references
References 125 publications
17
402
0
5
Order By: Relevance
“…Recent studies demonstrate that fungal species with a cosmopolitan distribution are the exception [66,67]. In general, most names applied to species with an apparent worldwide distribution probably represent species complexes rather than good species [68].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that fungal species with a cosmopolitan distribution are the exception [66,67]. In general, most names applied to species with an apparent worldwide distribution probably represent species complexes rather than good species [68].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, loss of a fungal entity within local community may be replaced by immigration of an individual from the regional metacommunity. Fungal communities usually display strong biogeographical patterns as a result of dispersal limitation at regional scale (Peay et al 2016). For instance, it has been shown that the geographic location of the production region shapes the structure of seed fungal OTUs with a lower (−1) and higher (+1) frequency than expected by the Sloan neutral model are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…This inoculum often comprises of soil taken from (presumably, fungal-rich) habitats and transferred to arable fields. Although the species-composition of native mycorrhizal communities may vary globally depending on local vegetation, elevation, climate, and soil chemistry, most AMF have low host-specificity (Lee et al, 2013; Veresoglou and Rillig, 2014; Peay et al, 2016). Since AMF readily form symbiosis with multiple plant species, mycorrhizae isolated from one location have the potentially to successfully colonize plants at other sites.…”
Section: Inoculum Synthetic Biology and The Development Of Fungal Chmentioning
confidence: 99%